SEISMIC FACIES STUDY ON THE TALANGAKAR FORMATION, JAMBI SUB-BASIN, SOUTH SUMATRA BASIN - Yulma Putra, Afif
The Jambi subbasin is a subbasin located in the South Sumatra Basin and is one of the main hydrocarbon producers in Indonesia. The Talangkar Formation is one of the formations that acts as a source rock and reservoir in the Jambi Subbasin. Oil and gas exploration has been carried out for more than a century and produces more than 1.5 billion barrels of oil and gas. However, the government is still expecting new discoveries in this area. Therefore, the study of seismic facies and well data was carried out to open new insights into the distribution of the Talangakar Formation on the subsurface. The methods used in this study include lithofacies analysis, electrofacies analysis, well to seismic tie, 3D seismic interpretation, seismic facies analysis, and depositional environment interpretation. The Talangakar Formation in the study area is dominated by claystone with siltstone, sandstone, and coal. Based on the analysis of architectural facies, the research interval is part of the meander river and the river-dominated delta. The analysis is correlated with seismic facies so that the distribution of the depositional environment is known. The results of the seismic facies analysis show that the research area has six seismic facies, namely seismic facies 1, 2, 3, 4, 5, and 6. These seismic facies are correlated with architectural facies. The correlation includes prodelta and floodplain architectural facies correlated with seismic facies 1, fan deltas correlated with seismic facies 2, delta plains and swamps correlated with seismic facies 3, distributary channels and river channels correlated with facies 4, delta fronts correlated with seismic facies 5, and floodplains correlated with seismic facies 6.